2020
DOI: 10.3389/fphys.2020.00051
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Perfluorooctanoic Acid Exposure Inhibits Placental Development by Dysregulation of Labyrinth Vessels and uNK Cells and Apoptosis in Mice

Abstract: Perfluorooctanoic acid (PFOA) is a widely used perfluorinated compound and known to cause developmental toxicity which includes the increase of resorbed embryo, decrease of fetal survival, and fetal growth retardation. Nevertheless, whether it is associated with alteration of placental development remains unknown. Pregnant mice were gavaged with 0, 2.5, 5, 10 mg PFOA /kg/day from pregnancy day (PD) 1 to PD 13. Results showed that PFOA exposure markedly decreased the placental weight and caused interstitial ede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Exposure to PFAS has also been shown to alter placental weight, disrupt its labyrinth structure, and induce congestion and clot formation ( Blake et al. 2020 ), as well as apoptosis ( Jiang et al. 2020 ), in in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to PFAS has also been shown to alter placental weight, disrupt its labyrinth structure, and induce congestion and clot formation ( Blake et al. 2020 ), as well as apoptosis ( Jiang et al. 2020 ), in in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that existing toxicologic evidence indicates that PFAS may alter processes that are implicated in early-onset disease, including trophoblast migration and invasion (Szilagyi et al 2020) and angiogenic processes (Pham et al 2020;Poteser et al 2020). Exposure to PFAS has also been shown to alter placental weight, disrupt its labyrinth structure, and induce congestion and clot formation , as well as apoptosis (Jiang et al 2020), in in vivo studies. In light of this mechanistic evidence, further consideration of the relationship between PFAS and preeclampsia subtypes is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…46 Several animal studies also demonstrated that apoptosis of placental cells may be involved in the etiology of placental hypoplasia and dysfunction. 47,48 The current study found that the apoptosis of placental trophoblast was significantly elevated in mice with gestational cholestasis, and deoxycholic acid (DCA)-treated primary mouse placental trophoblast cell and human trophoblast cell lines. These results suggest that the apoptosis of placental trophoblast cell may be the main mechanism leading to placental insufficiency and IUGR during gestational cholestasis.…”
Section: Discussionmentioning
confidence: 77%
“…The placenta is involved in the etiology of these pregnancy conditions ( Pijnenborg et al, 1991 ) and PFAS pass from the maternal to fetal compartments through the placenta ( Chen et al, 2017 ; Zhao et al, 2017 ; Wang et al, 2019 ). Perfluorooctanoic acid (PFOA) and ammonium perfluoro-2-methyl-3-oxahexanoate (the ammonium carboxylate salt of the chemical compound hexafluoropropylene oxide-dimer acid, HFPO-DA, commonly referred to as GenX) have been shown to cause histopathological lesions in the mouse placenta ( Blake et al, 2020 ; Jiang et al, 2020 ). While it is not well understood how maternal exposure to a few PFAS may contribute to adverse pregnancy outcomes, their effect(s) on placental function is likely critical and may extend to other untested PFAS ( Blake and Fenton, 2020 ; Rickard et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%